Excess Mortality in Kidney and Kidney-Pancreas Transplant Recipients in the COVID-19 Pandemic in Portugal—A Cohort Study - Miguel T. Coimbra; Miguel T. Coimbra; José A. T. S. Francisco; José A. T. S. Francisco; Joana C. Freitas; Renata V. Carvalho; Renata V. Carvalho; Sara R. B. Vilela; Sara R. B. Vilela; Catarina I. C. D. Ribeiro; José L. C. S. L. Silvano; Sofia Pedroso; et al. (Transplant International, 2023)
The COVID-19 pandemic increased morbidity and mortality worldwide, particularly in the Kidney and Kidney-Pancreas Transplant Recipient (KTR/KPTR) population. Aiming at assessing the absolute and relative excess mortality (EM) in a Portuguese KTR/KPTR cohort, we conducted a retrospective observational study of two KTR/KPTRs cohorts: cohort 1 (P1; n = 2,179) between September/2012 and March/2020; cohort 2 (P2; n = 2067) between March/2020, and August/2022. A correlation between relative and absolute EM and age, sex, time from transplantation and cause of death was explored. A total of 145 and 84 deaths by all causes were observed in P1 and P2, respectively. The absolute EM in P2 versus P1 was 19.2 deaths (observed/expected mortality ratio 1.30, p = 0.006), and the relative EM was 1.47/1,000 person-months (95% CI 1.11–1.93, p = 0.006). Compared to the same period in the general population, the standardized mortality rate by age in P2 was 3.86 (95% CI 2.40–5.31), with a peak at 9.00 (95% CI 4.84–13.16) in P2C. The higher EM identified in this population was associated, mainly, with COVID-19 infection, with much higher values during the second seasonal COVID-19 peak when compared to the general population, despite generalized vaccination. These highlight the need for further preventive measures and improved therapies in these patients.